2008
DOI: 10.1212/01.wnl.0000306696.82017.66
|View full text |Cite
|
Sign up to set email alerts
|

Plasma amyloid levels and the risk of AD in normal subjects in the Cardiovascular Health Study

Abstract: Plasma A beta levels are affected by age and by systemic and CNS vascular risk factors. After controlling for these conditions, A beta-40 and A beta 1-42 are weak predictors of conversion to Alzheimer disease (AD) in normal subjects and are only weakly associated with AD in cross-sectional analysis. Consequently, plasma levels of A beta do not seem to be useful biomarkers for AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(141 citation statements)
references
References 37 publications
11
124
0
4
Order By: Relevance
“…Increased Ab or Ab 1-42 levels have been shown to predict the development of AD [113,114]; however, other analyses have revealed no associations [115,116] or opposite [117] results. A low Ab 1-42 /Ab 1-40 ratio is assumed to predict future AD [113,118,119].…”
Section: Blood Prospective Candidate Biomarkersmentioning
confidence: 98%
“…Increased Ab or Ab 1-42 levels have been shown to predict the development of AD [113,114]; however, other analyses have revealed no associations [115,116] or opposite [117] results. A low Ab 1-42 /Ab 1-40 ratio is assumed to predict future AD [113,118,119].…”
Section: Blood Prospective Candidate Biomarkersmentioning
confidence: 98%
“…Aˇ42 and Aˇ40, which according to the majority of the researches do not show significant differences between AD and healthy subjects [63,71] or give ambiguous results [72,73], Aˇ42/Aˇ40 ratio which in the study carried out by Koyama et al [71], at odds with the one performed by Hansson et al [72], has shown decreased values in AD patients and ˛1-antichymotrypsin and various markers of inflammation which have not provided evidence about the potential for distinguishing between AD patients and healthy subjects [73].…”
Section: Blood Testsmentioning
confidence: 99%
“…Although NSAID interventions did not impact the predictability of Aβ 1-42 and the Aβ 1-42 /Aβ 1-40 ratio on MCI/AD risk, this finding does not preclude possible longterm influences of NSAIDs, which have recently been suggested to reduce AD incidence in the total ADAPT cohort (36). Previously, Lopez et al evaluated the influence of vascular risk factors, as measured by the presence of infarct detected by magnetic resonance imaging, cystatin C, and APOE, and found Aβ peptides to be weak predictors of AD (10). The parameters of vascular risk factors in the study by Lopez et al are different from those evaluated in the current study, which instead controlled for SBP, triglycerides, creatinine, and APOE and revealed that Aβ 1-42 and the Aβ 1-42 /Aβ 1-40 ratio are excellent predictors of AD.…”
Section: Characteristicsmentioning
confidence: 99%
“…Differences among studies in the duration of follow-up prior to conversion have led to differing results pertaining to the predictive value of Aβ toward AD onset and may be attributable to the changes in Aβ levels with preclinical disease progression (6,7 Likely reasons for these discrepancies may include population stratification or presence of confounding factors that are associated with AD and also influence Aβ levels. We and others have demonstrated that vascular risk factors of AD (and medications to treat these conditions) are associated with differences in blood Aβ levels (8)(9)(10)(11)(12)(13)(14). However, the consequences of such an association on the predictive value of Aβ for MCI/AD is underexplored, having been evaluated in only one longitudinal study thus far, after which the authors reported that Aβ showed little usefulness in AD prediction (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation